2001
DOI: 10.2214/ajr.176.6.1761521
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Perioperative Hypogastric Artery Balloon Occlusion in Abnormal Placentation

Abstract: We conclude that balloon occlusion of the hypogastric arteries is a safe and effective adjunct to cesarean hysterectomy in an attempt to minimize blood loss in patients with abnormal placentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
75
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 9 publications
1
75
1
4
Order By: Relevance
“…These successes were confirmed in further studies [18,21]. Kidney et al [23] showed reliable hemostasis with only minimal complications via temporary occlusion without particle embolization in the case of placenta accreta. Polytransfusions were needed in only one patient in another study by Li et al [8], while only a single blood transfusion and volume substitutions were sufficient in 12 of 21 patients [8].…”
mentioning
confidence: 76%
“…These successes were confirmed in further studies [18,21]. Kidney et al [23] showed reliable hemostasis with only minimal complications via temporary occlusion without particle embolization in the case of placenta accreta. Polytransfusions were needed in only one patient in another study by Li et al [8], while only a single blood transfusion and volume substitutions were sufficient in 12 of 21 patients [8].…”
mentioning
confidence: 76%
“…Hysterectomy can be performed 2 to 6 weeks later on an elective basis. Pelvic arterial embolization or balloon catheter occlusion significantly reduces uterine blood flow and allow reduced blood loss during surgery [6]. Other adjunctive procedures like methotrexate therapy, uterine compression sutures, internal iliac vessels embolization, resection of the affected segment of the uterus and oversewing of the placental bed may help [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…In most studies internal iliac artery balloons inflated immediately after delivery of the fetus [7]. The major anastomotic channels of the female pelvis will function after internal iliac artery balloon occlusion, thus balloon inflation provides only transient relief in intraoperative blood loss [7,16,18]. The reduction of blood flow to pelvic structures may be successful, although complete cessation of perfusion probably cannot be accomplished [16].…”
mentioning
confidence: 99%
“…Those patients, have significantly higher mean intraoperative blood loss and transfusion requirements as a result of the time and the efforts to avoid cesarean hysterectomy [7,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation